Prevalence and Pattern of Self‐Harm Among University Students in Dhaka: A Cross‐Sectional Study - Abdullah Muhammad Fariduzzaman; Zunayed Al Azdi; Sayedul Ashraf Kushal; Yahia Md Amin; Krishna Roy; Jhowhar Datta; Erina Tabassum; Jhunu Shamsun Nahar (Health Science Reports)
ABSTRACT Background Self‐harm remains a significant public health issue worldwide, with university students being particularly affected. This study examines its prevalence and associated factors among university students in Dhaka, Bangladesh, while considering broader global, regional, and local trends. Methods This study utilized a cross‐sectional design, surveying 200 students from the University of Dhaka and the Bangladesh University of Business and Technology. Data were gathered through in‐person interviews and analyzed using SPSS version 26. Results The study found that self‐harm was prevalent at 17%, with a striking gender difference—females exhibited a four times higher occurrence than males. Bivariate analysis indicated no significant variations across institutions, academic disciplines, habitat, or socioeconomic status. However, logistic regression revealed key associations: females were more prone to self‐harm, while middle and high socioeconomic status served as protective factors. Conclusion This study highlights the critical need for customized mental health programs targeting university students in Dhaka. The identified prevalence and influencing factors provide a foundation for future research and support the development of evidence‐based strategies to reduce self‐harm and promote overall mental well‐being on campus.